Access to justice through the Privy Council is restricted - Antoine, Rose-Marie B. (2000)
Focuses on the two main reasons why access to justice through the avenue of the Privy Council is excessively limited. Suggests how the Caribbean Court of Justice will improve on these aspects of access to justice.